2014
DOI: 10.1007/s00127-014-0826-z
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and comorbidity of psychiatric disorders among 6-year-old children: 2004 Pelotas Birth Cohort

Abstract: PurposeMost studies published on the prevalence of psychiatric disorders in children were conducted in high-income countries despite the fact that nearly 90 % of the world’s population aged under 18 live in low- and middle-income countries. The study aimed to assess the prevalence of psychiatric disorders among children of 6 years of age, to examine the distribution of psychiatric disorders by gender and socioeconomic status and to evaluate the occurrence of psychiatric comorbidities.MethodsThe 2004 Pelotas Bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
2
17

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 42 publications
5
46
2
17
Order By: Relevance
“…A higher female susceptibility has also been reported for the specific phobia fear of heights [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. The prepubertal children in the current study showed no gender predominance in susceptibility.…”
Section: Gender-specific Differences?supporting
confidence: 67%
See 1 more Smart Citation
“…A higher female susceptibility has also been reported for the specific phobia fear of heights [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. The prepubertal children in the current study showed no gender predominance in susceptibility.…”
Section: Gender-specific Differences?supporting
confidence: 67%
“…When the definition of "excessive fears and worries or phobias" was broadened, prevalence rates of 7 to 9% were found. A survey on the prevalence and comorbidity of psychiatric disorders among 6-year-olds revealed that specific phobias (without any specification of the subtypes, e.g., animal, natural environment, blood or injection injury) were the most common subtypes of anxiety disorders, having a frequency of 5.4% [12]. In another study on dishabituation processes in fear of heights in children, fear of heights was found to occur in 6.9% of children aged 11 years and in 19.1% of young adults aged 18 years, if moderate and severe forms were included [13].…”
Section: Discussionmentioning
confidence: 99%
“…A Norwegian study on psychiatric prevalence in the general preschoolers’ population found a 7.1% rate for any psychiatric disorder using a diagnostic parent interview (Wichstrøm et al, 2012). Similarly, a population study of Brazilian 6-year-olds found a prevalence of 8% in children from high-income families (Petresco et al, 2014). To our knowledge, no comparable prevalence studies have been conducted in that age group in the Netherlands.…”
Section: Discussionmentioning
confidence: 91%
“…Specific phobia (5 %) and separation anxiety disorder (3%) were the most prevalent anxiety disorders. 17 28.7% of the patients in our study had psychiatric comorbidities, i.e., dual psychiatric diagnosis. While the occurrence of more than one diagnosis was seen among (18.3 %) of the children in a study from Brazil.…”
Section: -14mentioning
confidence: 73%